Pengaruh Prestasi Belajar, Status Sosial Ekonomi Keluarga, Dan Minat Berwirausaha Terhadap Kesiapan Berwirausaha Siswa SMK - Rochani, Siti; Suharsono, Naswan (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This study aims to determine the effect of academic achievement, family socioeconomic status, and interest in entrepreneurship on the entrepreneurial readiness of class XII students in the field of Business Management at SMK Negeri 1 Lumajang. This research includes ex post facto research with a quantitative approach. Questionnaire data collection methods and documentation. The population and sample are 132 respondents. Data analysis used path analysis test using IBM SPSS version 20 for windows. Based on the results of the study with a significance level of 5%, it can be concluded: 1) Learning achievement has no significant effect on entrepreneurial interest with a significance value of 0.476 (> 0.05). (2) Family socio-economic status has a significant effect on interest in entrepreneurship with a significance value of 0.008 (<0.05). (3) Learning achievement on entrepreneurship readiness has no significant effect with a significance value of 0.694 (> 0.05). (4) Family socio-economic status on entrepreneurship readiness has no significant effect with a significance value of 0.810 (> 0.005). (5) Entrepreneurial interest has a significant effect on entrepreneurial readiness with a significance value of 0.000 (<0.005). (6) Learning achievement on entrepreneurship readiness through interest in entrepreneurship indirectly has a significant negative effect on student entrepreneurship readiness of -0.016 (<0.005). (7) Family socio-economic status on entrepreneurship readiness through entrepreneurial interest has a direct and significant negative effect on student entrepreneurship readiness of -0.107 (<0.005).